Quasi-Static Cyclic Test on a Concrete-Encased Frame-Reinforced Concrete Tube Building Model - Lei Zeng; Yunfeng Xiao; Juan Chen; Yiguang Chen (Shock and Vibration)
This paper experimentally investigated the seismic behavior of a 1:5 reduced-scale model of concrete-encased steel frame-reinforced concrete core tube building. The quasi-static testing with multipoint loading was carried out, and mode-superposition response spectrum method was adopted to control the amplitude of displacement. The damage process, crack pattern, and failure mode were observed. Various parameters were obtained, including lateral deformation, hysteretic characteristics, strain distribution, ductility, and energy dissipation capacity. The test revealed the distributions of base shear between the core tube and frame. The result indicated that the core tube bears major loading and exhibited overturning failure, afterwards frame carry the surplus load and exhibited column tensile failure and joint panel shear failure. The characteristic of two seismic resistant systems are reflected by the excellent cooperation of core tube and frame.